Aspek Etika dalam Pembuatan Nutrisi Hidroponik untuk Kangkung (Ipomoea aquatica) - Nurkhofifah, Indah; Sastra, Siti Fathiya Dwinda; Husniatunnisa, Husniatunnisa; Lubis, Khairiza; Situmorang, Nurbaity (Journal of Natural Sciences, 2025)
Water spinach (Ipomoea aquatica) is a nutritious vegetable and has great potential in hydroponic cultivation. However, the creation of appropriate and ethical nutrients for the growth of this plant is still a challenge. This study aims to analyze the application of ethics in the creation and optimal concentration of nutrients A and B needed by water spinach plants. The method used is an experimental approach at the Horticultural Seed Development Unit, Medan, during the period January to March 2025. Data collected include plant height, number of leaves, and fresh weight of plants. The results of the study indicate that the right concentration of nutrients can increase the growth of water spinach plants and ensure the safety of consumption. This study provides insight for farmers and hydroponic practitioners in improving the quality of water spinach cultivation.